SHAPE MEASURING APPARATUS AND METHOD - YOKOI KENSUKE (2018)
The invention discloses a shape measuring apparatus and method. In the shape measuring apparatus, an image processing unit derives, based on a calculated disparity, absolute distance information abouta first imaging target located in a common image region from a shape measuring apparatus. The image processing unit reconstructs a 3D shape of each of imaging subjects including the first and secondimaging subjects based on the sequential monochrome images. 公开了种形状测量设备和方法。在形状测量设备中，图像处理单元基于所计算的视差导出关于位于公共图像区域中的第成像对象距形状测量设备的绝对距离信息。图像处理单元基于序列单色图像重建包括第成像对象和第二成像对象的成像对象中的每个的3D形状。